2019
DOI: 10.3390/ijerph16224532
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of Tick-Borne Encephalitis Cycles in Warmer Climatic Conditions

Abstract: Tick-borne encephalitis exhibits profound inter-annual fluctuations in incidence. Previous studies showed that three-fifths of the variation can be explained in terms of four superimposed oscillations: a quasi-biennial, triennial, pentennial, and a decadal cycle. This study was conducted to determine how these cycles could be influenced by climate change. Epidemiological data, spanning from the 1970s to the present, and originating from six regions/countries bridging Scandinavia and the Mediterranean, represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The establishment of new permanent foci may depend on complex environmental requirements [35]. Among them, climate and climate change have been mentioned as important factors for the expansion or emergence of new TBEV foci [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of new permanent foci may depend on complex environmental requirements [35]. Among them, climate and climate change have been mentioned as important factors for the expansion or emergence of new TBEV foci [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…For example, TBE virus exhibits large interannual variations in prevalence and incidence related to interactions among host population cycles, host immunity, and longevity. Zeman (89) demonstrated cyclical oscillations in TBE virus in large areas of Europe (Sweden, Germany, the Czech Republic, Slovenia, Austria, and Italy) and showed that climate change alters the length of these cycles: Warmer conditions lengthen the cycle frequency due to increased host longevity reducing the speed of variation in host immunity, which feeds back into the level of TBE virus circulating in the host (and tick) population.…”
Section: Evidence For Climate Change Impacts On Tick-borne Diseasesmentioning
confidence: 99%
“…The temperature rise constitutes a risk of increased TBE cases from a possible transmission, which occurs during winter, as it causes the extension of the tick’s activity period during the winter months and consequently the reduction of the tick’s inactivity period. Moreover, the higher temperatures that occur as a result of climate change influence the length of the round fluctuations in TBEV in numerous European countries such as Sweden, Germany, Czech Republic, Slovenia, Austria, and Italy [ 82 ]. Τhe simultaneous blood meal of I. ricinus uninfected larvae and infected nymphs from a host correlates with the occurrence of TBE cases and depends on the rhythm of the temperature reduction in the autumn [ 21 ].…”
Section: The Effect Of Climate Change On the Prevalence Of Lb And Tbementioning
confidence: 99%